Functional Outcome of Herbert Screw Fixation with Bone Grafting in Scaphoid Nonunion - Saeed, Muhammad; Khan, Muhammad Zahid; Haq, Shafi Ul; Hussain, Majid (Biological and Clinical Sciences Research Journal, 2025)
Scaphoid nonunion is a frequent complication of missed or inadequately treated fractures that may lead to wrist instability and degenerative arthritis. Surgical fixation with a Herbert screw, combined with bone grafting, has emerged as an effective technique for promoting union and restoring function. Objective: This study aimed to evaluate functional outcomes following surgical management of scaphoid nonunion with Herbert screw fixation and autologous bone grafting. Methodology: Sixty patients with a clinically and radiographically confirmed diagnosis of scaphoid nonunion were enrolled. All participants underwent Herbert screw fixation with bone grafting under general anesthesia. Postoperatively, the wrist was immobilized for two weeks, followed by mobilizing exercises. The functional outcome was assessed at 60 days post-procedure using the Modified Mayo Wrist Score. Results: In our study, union was achieved in 56 (93.3%) patients. Thirty-six patients (60%) were rated as having an excellent result, while 20 patients (33.3%) achieved a good outcome. A fair result was observed in 3 patients (5%), and a poor outcome in only one patient (1.7%). Conclusion: Herbert screw fixation with bone grafting in scaphoid non-unions exhibited a favorable functional outcome and a higher success rate for union.